2011
DOI: 10.1371/journal.pone.0017644
|View full text |Cite
|
Sign up to set email alerts
|

Severe Airway Epithelial Injury, Aberrant Repair and Bronchiolitis Obliterans Develops after Diacetyl Instillation in Rats

Abstract: BackgroundBronchiolitis obliterans (BO) is a fibrotic lung disease that occurs in a variety of clinical settings, including toxin exposures, autoimmunity and lung or bone marrow transplant. Despite its increasing clinical importance, little is known regarding the underlying disease mechanisms due to a lack of adequate small animal BO models. Recent epidemiological studies have implicated exposure to diacetyl (DA), a volatile component of artificial butter flavoring, as a cause of BO in otherwise healthy factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 28 publications
13
52
0
Order By: Relevance
“…81,82 A decrease in Scgb1a1 transcripts has also been described in rats during the development of bronchiolitis obliteranselike changes after intratracheal instillation of diacetyl. 83 We believe that in our study, the decrease in Scgb1a1 mRNA results from a loss of club cells (previously known as Clara cells) in the airways of the diacetyl-exposed Dcxr ko2 mice. Consistent with that interpretation, ultrastructural documentation of autophagy was most prominent in club cells in our study.…”
Section: Protein Damage and Diacetyl Cytotoxicitymentioning
confidence: 57%
“…81,82 A decrease in Scgb1a1 transcripts has also been described in rats during the development of bronchiolitis obliteranselike changes after intratracheal instillation of diacetyl. 83 We believe that in our study, the decrease in Scgb1a1 mRNA results from a loss of club cells (previously known as Clara cells) in the airways of the diacetyl-exposed Dcxr ko2 mice. Consistent with that interpretation, ultrastructural documentation of autophagy was most prominent in club cells in our study.…”
Section: Protein Damage and Diacetyl Cytotoxicitymentioning
confidence: 57%
“…This contrasts with intratracheally instilled diacetyl, which resulted in significantly increased airway R L and decreased C dyn in rats 7 d after exposure (Palmer et al, 2011). Even more surprisingly, acute inhalation of the flavorings did not lead to airway hyperreactivity.…”
Section: Discussionmentioning
confidence: 69%
“…Histological investigation in animal models demonstrated that a 6-h exposure inhalation exposure to diacetyl and 2,3-pentanedione causes some epithelial damage 0 h postexposure, which progresses in intensity by 18 to 20 h postexposure (Hubbs et al, 2002(Hubbs et al, , 2008(Hubbs et al, , 2010(Hubbs et al, , 2012Morris and Hubbs, 2009;Morgan et al, 2008Morgan et al, , 2012aMorgan et al, , 2012bPalmer et al, 2011). In addition, inhaled 2,3-pentanedione was found to result in olfactory neuroepithelial injury in rats (Hubbs et al, 2012), and, interestingly, diacetyl may induce long-lasting neurotoxicity by binding to ÎČ-amyloid and interfering with pleated sheet structures (More et al, 2012a).…”
mentioning
confidence: 99%
See 2 more Smart Citations